2018
DOI: 10.1097/mcg.0000000000000893
|View full text |Cite
|
Sign up to set email alerts
|

Educational Colonoscopy Video Enhances Bowel Preparation Quality and Comprehension in an Inner City Population

Abstract: Our unique population represented an overwhelmingly under-educated (85% had a high school education or less) and minority group (76% African American). They are one of the most at risk of having multiple barriers such as comprehension and reading difficulties resulting in poor preparation examinations and no shows to procedures. Our instructional video proved to be high yield in this population. The patients assigned to watch the colonoscopy video showed a significant increase in "excellent" grade adequate bow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 12 publications
0
37
0
15
Order By: Relevance
“…Our search yielded a total of 2,148 potentially relevant clinical trials that used either educational video or conventional education methods on patients who underwent colonoscopy. After further review and screening, eight RCTs comprising of 1,977 subjects met the inclusion criteria (6,(19)(20)(21)(22)(23)(24)(25) and were pooled for the meta-analyses (Figure 1). The baseline characteristics of each trial are shown in Table 1.…”
Section: Characteristics Of Studies Included In This Studymentioning
confidence: 99%
“…Our search yielded a total of 2,148 potentially relevant clinical trials that used either educational video or conventional education methods on patients who underwent colonoscopy. After further review and screening, eight RCTs comprising of 1,977 subjects met the inclusion criteria (6,(19)(20)(21)(22)(23)(24)(25) and were pooled for the meta-analyses (Figure 1). The baseline characteristics of each trial are shown in Table 1.…”
Section: Characteristics Of Studies Included In This Studymentioning
confidence: 99%
“…The trial is aimed to explore whether VR videos can improve bowel preparation quality through increasing patient adherence and experience, and reduce pre-procedure anxiety, compared with the conventional patient education methods. To date, there have been several studies demonstrating that extensive patient education methods7–18 are effective in enhancing bowel preparation quality. However, there is a lack of evidence on the effect of VR videos, a novel technology which can arouse patients’ interests and motivation.…”
Section: Discussionmentioning
confidence: 99%
“…In most occasions, such education is offered only once through either oral or written instructions by clinicians during an initial appointment. Strong evidence has shown that extensive education methods, including booklet,7 telephone,8 9 message reminders,10 11 smartphone applications,12 13 social media14 and online videos,15–18 have been used to aid patient education with variable effectiveness. These methods can increase patient motivation which can improve bowel preparation quality 19.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen and Wieland [19] suggested that low health literacy may lead to inadequate preparation, which underscores the importance of making information accessible to people of all backgrounds. Educational videos are advantageous as they may be more accessible to those with low health literacy [20]. The methodology presented in this study allows for an evaluation of the information quality of 2 colonoscopy videos and for clearer judgments about how different resources compare with each other.…”
Section: Information Qualitymentioning
confidence: 99%
“…The advantages of some of these approaches are that they are widely accessible and cost less [38]. A video may have an additional advantage of being comprehensible to people of varying levels of health literacy [20]. Previous research has demonstrated that the comprehension of colonoscopy information is one factor that is related to health literacy and suggests the importance of developing materials for individuals with varying levels of health literacy [39].…”
Section: Principal Findingsmentioning
confidence: 99%